Cardiff English - Mees, Inger M. (ELOPE (Ljubljana), 2015)
This article describes a real time panel study of a small number of working and middle class female speakers recorded in Cardiff at three points in time over a period of 35 years. The first recordings were made in 1977 when the informants were ten years old. The second date from 1990 when they were young adults, and the third from 2011 when they had entered into midadulthood. The linguistic variables investigated were h-dropping and the realisation of /r/ as an approximant or tap. Three issues were addressed. First, the two variables were categorised into indicators or markers/stereotypes on the basis of social and stylistic variation. This served as a basis for the second question, which was to discover if the patterns of change over time were in accordance with those predicted by the literature, with indicators remaining stable and markers/ stereotypes being age-graded. Finally, we looked at individual variation.
Keywords: cardifska angleščina; družbena in stilistična raznolikost; družbena ozaveščenost; družbeni označevalci; jezikovne spremembe; jezikovne spremenljivke; opuščanje /h/; starostno razvrščanje; študije v realnem času